1990
DOI: 10.1007/bf00226187
|View full text |Cite
|
Sign up to set email alerts
|

Phosphoglucoisomerase-catalyzed interconversion of hexose phosphates: isotopic discrimination between hydrogen and deuterium

Abstract: The discrimination between the isotopes of hydrogen in the reaction catalyzed by yeast phosphoglucoisomerase is examined by NMR, as well as by spectrofluorometric or radioisotopic methods. The monodirectional conversion of D-glucose 6-phosphate to D-fructose 6-phosphate displays a lower maximal velocity with D-[2-2H]glucose 6-phosphate than unlabelled D-glucose 6-phosphate, with little difference in the affinity of the enzyme for these two substrates. About 72% of the deuterium located on the C2 of D-[1-13C,2-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
16
0
2

Year Published

1991
1991
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 9 publications
2
16
0
2
Order By: Relevance
“…2, step 2). This is in good agreement with the known leakiness of the intramolecular transfer during isomerization (9,18,19).…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…2, step 2). This is in good agreement with the known leakiness of the intramolecular transfer during isomerization (9,18,19).…”
Section: Resultssupporting
confidence: 90%
“…2 H NMR Spectroscopy-The 2 H NMR spectra were recorded with a Brucker DPX 400 spectrometer operating at 61.4 MHz and fitted with a 19 F field frequency locking device. The T 1 values were measured by using an inversion recovery sequence with 12 inversion time values ranging from 5 ms to 6 s and calculated using the T 1 calculation software provided.…”
Section: Materials-d-glucosementioning
confidence: 99%
“…First, 2 H incorporation at the level of mannose 6-phosphate isomerase (F6P 7 mannose 6-phosphate) can lead to 2 H enrichment of H1 position of glucose (33). The other possibility is intramolecular exchange of 1 H in position 1 of F6P with 2 H in position 2 of G6P (34). In contrast to earlier reports (1-2), we found that oxidation of glycerol in the citric acid cycle did not contribute significantly to energy production using a perfusion medium containing physiological amounts of other unlabeled substrates.…”
Section: Discussionmentioning
confidence: 99%
“…Les transferts de protons accompagnant les diffkrentes Ctapes de cette biotransformation suscitent encore de nombreux travaux (1)(2)(3)(4). I1 en est ainsi par exemple de l'isomerisation du glucose-6-phosphate (G-6P) en fructose-6-phosphate (F-6P) :…”
Section: Introductionunclassified
“…Le proton introduit en position pro-R provient a la fois du milieu et d'un transfert intramoltculaire (3,4). On ignore cependant avec certitude dans quelle proportion et quels sont les facteurs susceptibles de la modifier.…”
Section: Introductionunclassified